Rate-depending plastic deformation behaviour in a nickel-base alloy under hydrogen influence. (3rd November 2021) - Ebner, Anna Sophie; Plesiutschnig, Ernst; Clemens, Helmut; Pippan, Reinhard; Maier-Kiener, Verena
Abstract: Despite a lot of research activities, the influence of hydrogen on the plastic deformation process is controversially discussed and often underestimated. Therefore, in this work strain rate jump tests were performed, using an electrochemical nanoindentation setup to investigate the deformation processes in a nickel-based alloy 725 under the influence of hydrogen, with the aim of determining thermally activated parameters such as strain rate sensitivity and activation volume. A hydrogen-induced hardness increase of about 8% was detected for all applied strain rates. The measured increase in strain rate sensitivity and the decrease in activation volume could be related to short-range order effects, which can lead to a more localized deformation. Furthermore, the optical evaluation of the remaining imprints showed a clear change in the formation of the plastically deformed zone during hydrogen charging. These insights into the deformation behaviour give further understanding regarding hydrogen-induced localized plasticity. Graphical abstract: Image 1 Highlights: Nanoindentation strain rate jump tests prove influence of hydrogen on rate dependent plastic deformation. Hydrogen plays a crucial role on plastic deformation behaviour and pile-up formation. The findings can be related to the hydrogen-enhanced localized plasticity.